Factor Analysis of Time Deposits on Customer Interests at BMT UGT Nusantara Banyuanyar Probolinggo Branch - Niroh Qonita Tillah Maulana Malik Ibrahim; Bashori Alwi (Universitas Muhammadiyah Sidoarjo, 2022)
Customer satisfaction is very important in improving the quality or customer confidence in the improvement or development of Islamic financial institutions. This research has a purpose to see what the customers' perceptions of satisfaction with the distribution of ratios obtained from BMT UGT Nusantara Banyuanyar Branch and what factors influence customer interest in deposit products at BMT UGT Nusantara Banyuanyar Probolinggo Branch. The approach taken is a quantitative approach. The measuring instrument selected in this research is the Likert scale. The population used is the customers of BMT UGT Nusantara Banyuanyar Branch. Purposive sampling method is used to take samples. There are three sampling techniques based on characteristics, namely 1) Customers aged over 20 years, 2) Having time deposits, and 3) Having savings deposits for 1 year and over. Questionnaires were distributed to customers of BMT UGT Nusantara Banyuanyar Branch. A total of 53 samples is in line with the provisions of the characteristics of the determination of the sample. Testing the data taken in this research consisted the classical assumption testing (normality test, multicollinearity, and heteroscedasticity) as well hypothesis test (multiple regression analysis). The results of research on profit sharing, location, and social environment good impact on consumer interenst. Meanwhile, promotion and religiosity have no impact on customer interest. These results are said to be in the T test and the result are significantly less than 0.05 and greater than the T table.